Pengaruh Kepercayaan dan Kemudahan Penggunaan Terhadap Keputusan Penggunaan Aplikasi OVO (Survei Pada Generasi Z di Jakarta Pusat) - Safitri, Annisa; Firmansyah, Ade (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to determine and analyze the influence of Trust and Ease of Use on the Usage Decision of the OVO application. This research is a quantitative study. The research sample consisted of 100 respondents, selected using Purposive Sampling. Data collection technique employed a questionnaire that had been tested for validity and reliability. The data analysis used multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results of this study indicate that based on the t- test, both Trust and Ease of Use variables have a significant partial effect. Simultaneously, both Trust and Ease of Use variables have a positive and significant effect on the Usage Decision of the OVO application (a survey among Generation Z in Central Jakarta).